Samfundsøkonomisk analyse af en fast forbindelse over Femern Bælt - Bøgelund, Mette (Proceedings from the Annual Transport Conference at Aalborg University, 2004)
The analysis comprises a detailed cost-benefit analysis of a fixed link across the Femern Belt. The analysis is based upon existing detailed traffic forecasts. It is based upon official Danish cost-benefit metodology which is documented in detail in a metodology appendix.